РЕШЕНИЕ ПРОБЛЕМ, СВЯЗАННЫХ С ОСУЩЕСТВЛЕНИЕМ ОРГАНИЗАЦИОННЫХ ИЗМЕНЕНИЙ И С РАЗВИТИЕМ ГОСУДАРСТВЕННОГО СЕКТОРА ПАКИСТАНА - РизвиС. А. А.; АрифМ.; ФиазС.; АбидинЗ. Ul; НурС. (Вопросы государственного и муниципального управления, 2025)
Pakistan is at a crucial stage in the process of undergoing a political, social, and economic transformation. The performance of the public sector has a significant impact on the population. The public sector is undergoing consistent reform and development due to the requirements of the time. This study aims to locate and understand the elements that inhabit organizational transformation and development in Pakistan’s public sector. We adopted qualitative techniques and thematic analysis to find insights and answers to the research questions. The case study approach was utilized, and semi-structured interviews were conducted with 21 public servants who have been part of the change process at public entities. The most significant factors of the research study relate to socioeconomics, the progression of technology, willingness for change, cultural effect, political will, the impact of elite decision-makers, and the improvement of administrative systems. These main themes have a significant impact on the progression of the process As an outcome of the study, we have developed a holistic model to understand public management reforms in Pakistan. This study will serve as a road map for policymakers to facilitate their decision-making process. Moreover, this is also beneficial for researchers in the public management field, legislatures, and various public entities. The research enhanced an understanding of institutional theory regarding organizational, change, transformation and development, within Pakistani public sector organizations.